Using the impact-WEB_GIS platform to assess the impacts of environmental sustainability public policies in the Lisbon Metropolitan Area - Medeiros, E.; Valente, B.; Pinto, R.; Dias, J. (Sustainability, 2023)
Urban environmental sustainability is a growing concern within the United Nations and the European Union’s ongoing policy agendas to fight climate change. This paper contributes to this debate by presenting the main impacts of the Operational Programme for Sustainability and Use of Resources (POSEUR 2014–2020) in the Lisbon Metropolitan Area (NUTS II). The analysis was completed using the Impact-WEB_GIS platform, specially developed for this study, supported by a territorial impact assessment methodology. In addition to the production of general impact scores, five analytic dimensions were further analysed, supported by state-of-the-art (i) low-emissions economy, (ii) adaptation to climate change, (iii) risk prevention and management, (iv) environmental protection and (v) resource efficiency. At a strategic level, the research created awareness of the need to adjust regional policy to the region’s characteristics on environmental sustainability matters.